Pharmacogenomics of analgesics in anesthesia practice: A current update of literature - Keith Gray; Sanjib D Adhikary; Piotr Janicki (Wolters Kluwer Medknow Publications, 2018)
The field of pharmacogenomics seeks to understand how an individual's unique gene sequence can affect their response to certain drugs. It is particularly relevant in anesthesia when the interindividual response to pain medication is essential. Codeine and tramadol are prodrugs metabolized by CYP2D6, polymorphisms of which can cause dangerous or even fatal levels of their metabolites, or decrease the level of metabolites to decrease their analgesic effect. Many other opioids are metabolized by CYP2D6 or CYP3A5, of which loss-of-function variants can cause dangerous levels of these drugs. The OCT1 transporter facilitates the movement of drugs into hepatocytes for metabolism, and variants of this transporter can increase serum levels of morphine and O-desmethyltramadol. Many NSAIDs are metabolized by CYP2C9, and there is concern that variants of this enzyme may lead to high serum levels of these drugs, causing gastrointestinal bleeding, however the data does not strongly support this. The ABCB1 gene encodes for P-glycoprotein which facilitates efflux of opioids away from their target receptors. The C3435T SNP may increase the concentration of opioids at target receptors, although the data is not conclusive. Catechol-O-Methyltransferase (COMT) is shown to indirectly upregulate opioid receptors. Certain haplotypes of COMT have been demonstrated to have an effect on opioid requirements. The OPRM1 gene codes for the mu-opioid receptor, and there is conflicting data regarding its effect on analgesia and opioid requirements. Overall, there is a fair amount of conflicting data in the above topics, suggesting that there is still a lot of research to be done on these topics, and that pain perception is multifactorial, likely including many common genetic variants.